Pendidikan Kesehatan tentang Penyakit Leptospirosis pada Siswa SMA - Etik Lusiani; Irine Yunila Prastyawati; Adventia Nobita (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Leptospirosis is a zoonotic disease caused by Leptospira interrogans infection of all serotypes. The transmission of Leptospirosis occurs due to poor environmental conditions and this incidence increases in conditions of natural disasters, that is, floods. Leptospirosis has a bad impact on health because someone who is exposed can experience lung problems, kidney problems, or bleeding in the body. There are several high school students in grades 10-12 who have never received information about Leptospirosis, which is one of the effects of the flood disaster. This condition is necessary for the millennial generation to care about preventing Leptospirosis and contributing to flood disaster management activities. Information on preventing Leptospirosis is provided through community service activities. The process of this activity starts with the principal of a high school in Surabaya submitting a letter of application to provide health information to the LPPM STIKES Catholic unit of St Vincent a Paulo, then obtaining permission and carrying out community service activities. The results after the health education process were that there was a change in the level of knowledge of respondents, where before the activity, 17 people (57%) had less knowledge of respondents, 10 (33%) had sufficient knowledge and 3 (10%) had good knowledge of disease. Leptospirosis. The level of knowledge after being given health education 19 people (64%) had sufficient knowledge, 10 people (33%) had good knowledge and 1 person had less knowledge (3%). Based on these activities, it shows that health education can increase respondents' knowledge about Leptospirosis